Políticas de ações afirmativas para acesso e permanência de estudantes quilombolas em instituições federais de Mato Grosso - Lima, Luciana Gonçalves de (2025)
The thesis research presented here is linked to the Postgraduate Program in Education at the Federal University of Mato Grosso, in the line of research “Social Movements, Politics and Popular Education”, and was developed in the Group of Studies and Research in Quilombola Education (GEPEQ), coordinated by Prof. Dr. Suely Dulce de Castilho. The study discusses affirmative action policies aimed at the access and retention of black quilombola students in undergraduate courses at the Federal Institute of Education, Science and Technology of Mato Grosso (IFMT) and at the Federal University of Mato Grosso (UFMT), from 2015 to 2022/1. It aims to understand the trajectories and challenges faced by this group of students at IFMT and UFMT via affirmative action. The central question of the research is: how has the trajectory of quilombola quota students in the Federal Higher Education Institutions (IFES) of Mato Grosso been oulined? Methodologically, this study is based on a qualitative approach, from the perspective of participatory research. The main resources used to gather, record and produce the data include questionnaires, interviews, visits and observation at UFMT and IFMT units, field notebooks, participation in events, image records, audio recordings and transcriptions. The research was authorized in 2021/2 by the Human Research Ethics Committees of UFMT and IFMT. The theoretical foundations are based on decolonial epistemologies, in dialogue with post-colonial critical social theories and the interweaving of participants’ voices, which give meaning to the conceptual movement. The results reaffirm the relevance of the quota policy established by Federal Law No. 12.711/2012, which has expanded access to universities for quilombolas over the last decade. Between 2004 and 2021/1, sixteen federal universities implemented affirmative action, driven by the engagement of the Black and Quilombola Social Movements, which were significant in strengthening the struggles to expand Law No. 12.711/2012. In 2023, quilombolas were included as a specific group in the ethnic/racial sub quota, making it mandatory for all IFES to offer vacancies to this population. In this scenario, the National Student Assistance Program (PNAES) and the Bolsa Permanência Program (PBP/MEC) stand out as the main retention policies administered by IFES to assist these students. However, black quilombola quota students still face challenges, such as difficulties with the application format, understanding the communication/language of the calls for applications, the contents of the exams, etc. As for university retention, the students reported socioeconomic and technological barriers, difficulties with the written and oral content of university life and expressions of racism in academic relations. The voices of social workers, managers of the IFES surveyed and local leaders of the Black and Quilombola Movement show the historicity of collective struggles, the limits and difficulties in making public policy operational in Mato Grosso.